Answer: 4y + x - 22 = 0
Explanation:
Recall that for two lines to be perpendicular m1m2 = -1 ie, the product of their gradients must = -1
from the equation given, y - 3 = 4(x + 2), we need to rearrange it in the form
y = mx + c in order for us to ascertain the gradient.
y -3 = 4x + 8
y = 4x + 8 + 3
y = 4x + 11
Therefore, m1 = 4 while m2 = -1/4
The coordinate of the line = (-2, 6) . We now use this to find the value of c.
6 = -1/4 x -2 + c
6 = 1/2 + c
multiply by 2
12 = 1 + 2c
12 - 1 = 2c
11 = 2c
c = 11/2
now to find the equation of the second line
y = -x/4 + 11/2
now multiply through by 4
4y = -x + 22
4y + x - 22 = 0 is the required equation